Burnout em residentes multiprofissionais em saúde e as estratégias de enfrentamento - Oliveira, Rosângela Fernandes de (2019)
Burnout Syndrome among health care workers can be due to emotional and interpersonal reactions caused by the high levels of stress they deal with on a daily basis. This study aimed at identifying the presence of Burnout Syndrome among multiprofessional health residents. This is a descriptive research study, with quantitative and qualitative approach, carried out with multiprofessional health residents in public hospitals located in the city of Goiânia-Goiás. The following instruments were used: The Burnout Syndrome Inventory ISB (Benevindes-Pereira, 2015) with 6 dimensions (positive and negative organizational conditions, emotional exhaustion, emotional detachment, dehumanization and professional achievement), associated with the evaluation of sociodemographic characteristics such as: Gender, Marital Status, Profession, Previous Job, Moving Home, Living Alone, Number of Children, Studying, Enjoying Leisure Activities, Physical Activity, Having a Religion, Therapy, Undergoing a Medical Treatment. Following the quantitative outcomes, the focus group was carried out: work-related stress issues regarding residency. The logistic regression method was used in order to verify the association between these characteristics and the diagnosis of Burnout Syndrome. Outcomes: 134 residents participated in this research. Data was collected from September to December 2017. Outcomes: the survey showed that Emotional Exhaustion is present in 91% of the participants, Emotional Detachment in 89.6%, Dehumanization, 61.9%, Professional Achievement in 11.2%, Positive Organizational Conditions in 85.1% (114), and Adverse Organizational conditions in 82.1%. Association was observed with concurrent courses, male, living alone. After analysis of the focus group the following categories were evident: power, working conditions, difficulty in recognizing and coping strategies. Conclusion: a high prevalence of Burnout Syndrome was found in the group with stress response defined by the presence of exhaustion, detatchment, dehumanizing. The perception of professional achievement remains independent on stress.